Somatic, mood, and vasomotor symptoms at midlife in relation to family structure and household workloads in Sylhet, Bangladesh - Sharmeen, Taniya; Sievert, Lynnette Leidy; Begum, Khurshida; Chowdhury, Osul; Muttukrishna, Shanthi; Bentley, Gillian R. (Anthropological Review, 2013)
The purpose of this study was to test whether the frequencies of vasomotor, somatic, and emotional symptoms at midlife were associated with household composition or workloads. Patrilocal family arrangements are common in Bangladesh and, since mothers-in-law hold a position of power vis-à-vis their daughters-in-law, we hypothesized that living with a mother-in-law would increase the likelihood of symptoms at midlife, while living with a daughter-in-law would decrease likelihood of symptoms. We also hypothesised that women with high levels of household workloads would be more likely to report symptoms associated with midlife.Women aged 35–59 living in Sylhet, Bangladesh, (n=157) participated in interviews and anthropometric measures. Symptom frequencies during the past two weeks were collected. Household workloads were computed as minutes spent in housework, caring for dependents, and cooking. Daily values were multiplied by times per week the activity was carried out. Logistic regression was used to evaluate the association between family composition, workloads, and symptoms.Dizzy spells, nervous tension, lack of energy, aches/stiffness in joints, and trouble sleeping were most frequent. Hot flashes were reported by 46% of participants. Women spent more hours caring for dependents than cooking or doing housework. The likelihood of hot flashes increased with time spent in housework and cooking, with daughters in the household, and with chewing betel nut. Daughters-in-law in the household decreased the likelihood of hot flashes. The likelihood of nervous tension increased with peri-menopausal status, stress, and sons in the household, and decreased with more hours spent caring for dependents.The frequency of somatic symptoms and depressed mood exceeded the frequency of hot flashes. Household composition and workloads were more important than menopausal status in explaining variation in symptom frequencies. After controlling for other variables, the presence of mothers-in-law did not increase the likelihood of reporting symptoms at midlife; however, the presence of a daughter-in-law reduced the likelihood of hot flashes, perhaps because of fewer hours spent on housework and cooking.